2016
DOI: 10.1097/mca.0000000000000344
|View full text |Cite
|
Sign up to set email alerts
|

Clinical impact of thrombus burden in patients with ST-segment elevation myocardial infarction

Abstract: The first primary percutaneous coronary intervention (PCI) in ST-segment elevation myocardial infarction (STEMI) was performed in the early 1980s, and it is now the established and preferred therapeutic option for patients with STEMI [1,2]. Intracoronary thrombus subsequently developed at the site of plaque rupture is the essential mechanism of acute coronary occlusion in STEMI patients, and it is observed in more than 90% of the culprit lesions on the emergency coronary angiography. Thus, the management of re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…Our study findings were consistent with results of other researches presenting that angiographic evidence of coronary thrombi as a proven indicator of poor hospital course and adverse cardiac events [ 14 ]. In reality, distal embolization of thrombotic constituents or primary PCI-induced or spontaneous occlusion of epicardial vessels might compromise not only coronary but also myocardial perfusion [ 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…Our study findings were consistent with results of other researches presenting that angiographic evidence of coronary thrombi as a proven indicator of poor hospital course and adverse cardiac events [ 14 ]. In reality, distal embolization of thrombotic constituents or primary PCI-induced or spontaneous occlusion of epicardial vessels might compromise not only coronary but also myocardial perfusion [ 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…Adverse impacts of HTB are well established in previous studies in that HTB is a significant independent predictor for mortality and MACE and the size of the intracoronary thrombus is also associated with worse clinical outcomes, such as no reflow phenomenon, distal embolization, and lower procedural success. 3,31,32 In patients with STEMI, HTB, subsequent distal embolization and myocardial noreflow remain as a large obstacle that may negate the benefits of urgent coronary revascularization. 33 However, none of these studies specifically referred the impact of HTB in young STEMI patients.…”
Section: Adverse Impact Of Higher Tb In Young Stemi Patients In Chinamentioning
confidence: 99%
“…Clinical studies demonstrated that intracoronary thrombus challenges periprocedural success regardless of the underlying mechanism. HTB is related to distal embolization, no-reflow microvascular obstruction, inadequate reperfusion, subsequent myocardial damage, and deterioration of ventricular function 5,6,[18][19][20] . However, patients with HTB experience more stent thrombosis, recurrent MI, and recurrent revascularization 17,21 .…”
Section: Discussionmentioning
confidence: 99%
“…Higher thrombus burden in the course of AMI worsens outcomes both during the procedure and in the long term 5 . Despite the developing interventional techniques and more potent antithrombotic treatments, patients with higher thrombus burden have higher procedural complications such as no-reflow and distal embolism also; these patients have a more extended hospital stay, increased risk of stent thrombosis, recurrent AMI, heart failure (HF) and malignant arrhythmias 6 .…”
Section: Introductionmentioning
confidence: 99%